Proyecto de restauración y reciclaje de casa habitación en Puruándiro, Michoacán - Pantoja Iturbide, Diego (Universidad Michoacana de San Nicolas de Hidalgo, 2014)
The cultural architectural heritage is not exclusively in large symbolic, monumental buildings, you can also see so immersed in residential architecture of a site. This document presents a restoration project and recycling room house in Puruándiro, Michoacán, whose construction stage is the nineteenth and twentieth century encounters various effects caused by disuse and the different agents of deterioration that are causing havoc in serious the property. The aim is to continue maintaining a magnificent specimen, a witness to history and traditional architecture Puruándiro, which has given identity to the city, for the simple reason of keeping the architecture with which it was originally built. The work basically presents a comprehensive and multidisciplinary architectural project that contains the theoretical and technical foundation and the necessary methodologies for restoration of a house listed building, with traditional construction features, that responds to new needs that society demands in that area of the specific city, thus it was proposed to change the original use, by one tourist, as the current use does not promote the conservation of the property, this decision was based on the various analyzes and studies on the potential of the house. Also the construction of contemporary spaces that immediately distinguish when viewed by customers of the restaurant and cafeteria is suggested. The intervention is structured with theoretical principles of restoration, such as reversibility, conservation in situ and not fake, plus security systems such as sensors and fire extinguishers were proposed, the different areas were adapted for people with disabilities, plus a secluded smoking area and finally proposed in document strategies in the short, medium and long term management of the project in order to have higher chances of that project make it work from the work cited to the operation of the restaurant and cafeteria.

El patrimonio arquitectónico cultural no se encuentra única y exclusivamente en las grandes edificaciones simbólicas, monumentales, también se puede apreciar de forma inmersa en la arquitectura habitacional de un sitio. El presente documento expone un proyecto de restauración y reciclaje de una casa habitación en Puruándiro, Michoacán, cuya etapa de construcción es del siglo XIX y XX que se encuentra con diversas afectaciones por el desuso y los diferentes agentes de deterioro que están ocasionando serios estrago en el inmueble. La finalidad es continuar conservando un magnífico ejemplar, testigo de la historia y la arquitectura tradicional Puruándiro, que ha dado identidad a la ciudad, por la simple razón de mantener la arquitectura con la cual se construyó originalmente. El trabajo básicamente plantea un proyecto arquitectónico integral y multidisciplinario que contiene los fundamentos teóricos y técnicos así como la metodologías necesaria para realizar la restauración de una vivienda catalogada como monumento histórico, con características constructivas tradicionales, para que dé respuesta a nuevas necesidades que la sociedad demanda en esa zona de la ciudad específicamente, por ende se propuso cambiar el uso original, por uno turístico, ya que el uso actual no favorece la conservación del inmueble, dicha decisión se fundamentó en los diversos análisis y estudios sobre la potencialidad de la casa. Así mismo se sugiere la construcción de espacios contemporáneos que se distingan inmediatamente al ser observados por los clientes del restaurante y de la cafetería
Facultad de Arquitectura. Especialidad en Restauración de Sitios y Monumentos
Keywords: info:eu-repo/classification/cti/4; FA-E-2014-1563; Conservación; Adecuación; Sustentabilidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3194